"Driving Down a Road and Not Knowing Where You're At": Navigating the Loss of Physical and Social Infrastructure After the Camp Fire. (17th September 2021) - Brown, Adrienne R.
Abstract: Climate‐related disasters are becoming increasingly frequent and destructive. These events result in extensive material losses, but also more abstract disruptions, such as those to identity, well‐being, and community. Using transcripts from 24 qualitative interviews with residents of Paradise, California after a wildfire destroyed their town; I consider the changes to residents' physical and social infrastructure. Physical places provide a structure for social life to play out, and their familiarity offers feelings of belonging and security. But, relationships, routines, and personal histories also inscribe meaning and value on these spaces. After disaster, the loss of physical landmarks hinders residents' ability to navigate their community and inhibits social connections that would otherwise offer important supports. At the same time, new meanings become inscribed on existing places, through trauma reminders (which constrain social life) and positive cues from the natural world (which shift meanings from destruction‐ to recovery‐oriented). Because physical places are imbedded in social context, and vice versa, I examine these processes in tandem.